Corrosion-resistant concrete material and production process thereof

By adding hyperbranched organosilicon to concrete materials, and utilizing the synergistic effect of cage-like borate esters and imidazole rings, an organic-inorganic hybrid protective layer is formed, which solves the problems of insufficient corrosion resistance and environmental pollution, and achieves high-efficiency corrosion resistance and stability.

CN120987606APending Publication Date: 2025-11-21NINGBO DONGXING ASPHALT PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511109651.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-08
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing corrosion-resistant concrete materials have insufficient durability in complex corrosive environments, poor construction adaptability, and pose environmental pollution risks.

Method used

Hyperbranched organosilicon is used as a corrosion-resistant additive. Through the synergistic effect of cage-like borate ester structure, imidazole ring and free silanol groups, an organic-inorganic hybrid protective layer is formed at the steel/concrete interface, which hinders the penetration of corrosive ions and enhances the interfacial bonding force.

Benefits of technology

It significantly improves the corrosion resistance of concrete materials, reduces porosity, slows down the corrosion process, enhances the stability of the steel reinforcement protective layer, and reduces the risk of environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005539478790000091
    Figure BDA0005539478790000091
Patent Text Reader

Abstract

The invention relates to the technical field of concrete materials, and discloses a corrosion-resistant concrete material and a production process thereof. The concrete material prepared by the preparation method disclosed by the invention is prepared from the following raw materials in parts by weight: 70 to 90 parts of Portland cement, 175 to 205 parts of coarse aggregate, 80 to 110 parts of fine aggregate, 10 to 15 parts of fly ash, 5 to 10 parts of slag powder, 3 to 6 parts of hyperbranched organic silicon, 1.5 to 3.5 parts of a water reducing agent and 35 to 45 parts of water. By utilizing the synergistic effect of a cage-shaped borate structure, an imidazole ring and free silicon hydroxyl, an organic-inorganic hybrid protection layer is formed on a reinforcing steel bar / concrete interface, the physical barrier function and the chemical passivation function are achieved, and the corrosion resistance of a concrete material can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of concrete materials, and particularly relates to a kind of corrosion-resistant concrete materials and production process thereof. BACKGROUND

[0002] As the most widely used building material in the world, concrete is widely used in the fields of building, bridge, tunnel, marine structure and the like due to its high strength, durability and economy. However, there are a large number of pores in the concrete material, which provide a penetration channel for corrosive media under corrosive conditions such as chloride salt environment (such as marine engineering, deicing salt section), sulfate salt erosion (such as groundwater, chemical plant) and carbonation (such as industrial atmospheric environment), resulting in easy deterioration of concrete structure, leading to steel corrosion, protective layer peeling and ultimately shortening the service life.

[0003] The existing corrosion-resistant concrete material mainly improves the corrosion resistance by improving the compactness of the concrete, using epoxy coated steel bars, adding chemical admixtures (such as nitrite rust inhibitor or organic rust inhibitor) and coating a hydrophobic coating on the surface of the concrete material. However, the existing methods have the following problems in terms of long-term corrosion resistance, environmental friendliness and economy: (1) single protection mechanism: only relying on physical barrier or chemical passivation, which is difficult to cope with complex corrosion environment; (2) insufficient durability: organic rust inhibitor is easy to migrate and fail, and inorganic rust inhibitor (such as nitrite) may pollute the environment; (3) poor construction adaptability: some technologies (such as coated steel bars) have strict requirements on construction process. SUMMARY

[0004] In order to solve the above technical problems, the present application provides a kind of corrosion-resistant concrete material and production process thereof.

[0005] The object of the present application can be achieved by the following technical solutions:

[0006] A kind of corrosion-resistant concrete material, comprising the following raw materials by weight: Portland cement 70-90 parts, coarse aggregate 175-205 parts, fine aggregate 80-110 parts, fly ash 10-15 parts, slag powder 5-10 parts, hyperbranched organosilicon 3-6 parts, water reducing agent 1.5-3.5 parts, water 35-45 parts;

[0007] Further, the coarse aggregate is gravel with a particle size of 12-25 mm, and the fine aggregate is sand with a particle size of 2-6 mm;

[0008] Further, the water reducing agent is tartaric acid;

[0009] The hyperbranched organosilicon is prepared by the following steps:

[0010] Step A1, mix boronic acid and toluene, stir until uniform, add pentaerythritol, heat to 110℃, keep constant temperature, reflux for 8-10h, remove toluene and water by azeotropic distillation, add sodium hydroxide and tetrahydrofuran, pass nitrogen, heat and stir until reflux, then add 3,5-dibromoaniline, condense and reflux for 3-4h, wash, dry with anhydrous sodium sulfate, and distill under reduced pressure to obtain amino-terminated bis-caged borate ester;

[0011] Further, in step A1, the amount ratio of boronic acid, toluene, pentaerythritol, sodium hydroxide, tetrahydrofuran and 3,5-dibromoaniline is 0.02-0.04mol:50mL:0.02-0.04mol:1-2g:50mL:0.01-0.02mol;

[0012] Step A2, uniformly disperse 1,4-dichlorobutane and half of sodium hydroxide in DMF, add imidazole, and heat to 45℃, stir for 24h, then add amino-terminated bis-caged borate ester and the remaining half of sodium hydroxide, heat to 70℃, stir for 3-5h, distill under reduced pressure, and dry to obtain imidazole-bis-caged borate ester;

[0013] Further, in step A2, the amount ratio of 1,4-dichlorobutane, sodium hydroxide, DMF, imidazole and bis-caged borate ester is 1.34-4.1mL:1.8-5.4g:100mL:0.68-2.04g:3.66-10.1g;

[0014] Step A3, under nitrogen, mix 3-chloropropyltriethoxysilane, DMF and triethylamine, stir until uniform, add imidazole-bis-caged borate ester, heat to 85℃, reflux for 4h, rotary evaporate, and dry to obtain a modifier;

[0015] Further, in step A3, the amount ratio of 3-chloropropyltriethoxysilane, DMF, triethylamine and imidazole-bis-caged borate ester is 2.4-4.8mL:100mL:1.5-3mL:5.24-10.5g;

[0016] Step A4, mix tetraethyl orthosilicate, dimethyldimethoxysilane and ethanol, pass nitrogen, add water, heat to 60℃, reflux for 1-2h, then add the modifier, maintain the temperature, reflux for 2-3h, and rotary evaporate to obtain a hyperbranched organosilicon;

[0017] Further, in step A4, the amount ratio of tetraethyl orthosilicate, dimethyldimethoxysilane, ethanol, water and the modifier is 12-20g:8-15g:40mL:3.5-6.5g:8-16g.

[0018] A production process of a corrosion-resistant concrete material includes the following steps:

[0019] Step S1: Weigh the raw materials according to the weight parts, and mix the silicate cement, coarse aggregate, fine aggregate, fly ash and slag powder evenly to obtain the mixture;

[0020] Step S2: Add water-reducing agent, hyperbranched organosilicon and water to the mixture and stir to obtain corrosion-resistant concrete material.

[0021] The beneficial effects of this invention are:

[0022] The concrete material prepared by this invention, by adding hyperbranched organosilicon as a corrosion-resistant additive, utilizes the synergistic effect between the cage-like borate ester structure, imidazole ring, and free silanol groups to form an "organic-inorganic hybrid protective layer" at the steel / concrete interface, which has both physical barrier and chemical passivation functions, and can significantly improve the corrosion resistance of the concrete material.

[0023] The introduction of hyperbranched organosilicon can utilize its highly branched three-dimensional network to form a dense hydrophobic film in concrete pores, hindering the formation of Cl-. - SO4 2- The penetration of corrosive ions and water molecules is facilitated, and the free silanol groups can form chemical bonds with cement hydration products, enhancing interfacial bonding and reducing microcrack propagation. Cage-like borate esters slowly hydrolyze under alkaline conditions in concrete, releasing borate ions and organic components. Borate ions react with iron ions on the steel reinforcement surface to form a dense iron borate composite passivation film, enhancing the stability of the original oxide film and inhibiting the electrochemical dissolution of iron. Borate ions are preferentially adsorbed at the active sites of the steel reinforcement, hindering the absorption of chloride ions. - SO4 2- Contact with corrosive ions slows down corrosion; the nitrogen atom in the imidazole ring has proton acceptor ability, which can neutralize the acidic environment generated by concrete carbonation, delay the depassivation of steel bars, and can also form coordination bonds with the steel bar surface through π electrons, adsorbing to form an organic protective layer and inhibiting oxygen reduction reaction. In addition, cage-like borate esters can effectively block the capillary pores of concrete, reduce porosity, and inhibit Cl- - SO4 2- The diffusion of corrosive ions further improves the corrosion resistance of concrete. Detailed Implementation

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] In this embodiment, the coarse aggregate is crushed stone with a particle size of 12-25mm, the fine aggregate is sand with a particle size of 2-6mm, the water-reducing agent is tartaric acid, and the silicate cement is type II silicate cement with a particle size of PO42.5.

[0026] Example 1: Hyperbranched organosilicon was prepared by the following steps:

[0027] Step A1: Mix 0.02 mol boric acid and 50 mL toluene and stir until homogeneous. Add 0.02 mol pentaerythritol and heat to 110 °C. Recycle under constant temperature for 8 h. Remove toluene and water by azeotropic distillation. Add 1 g sodium hydroxide and 50 mL tetrahydrofuran. Purge with nitrogen gas and heat and stir until refluxed. Add 0.01 mol 3,5-dibromoaniline and reflux for 3 h. Wash, dry with anhydrous sodium sulfate, and distill under reduced pressure to obtain amino-terminated bis-cage borate ester.

[0028] Step A2: Disperse 1.34 mL of 1,4-dichlorobutane and 0.9 g of sodium hydroxide evenly in 100 mL of DMF, add 0.68 g of imidazole, heat to 45 °C and stir for 24 h, then add 3.66 g of terminal amino-biscage boronic acid ester and the remaining 0.9 g of sodium hydroxide, heat to 70 °C and stir for 3 h, distill under reduced pressure and dry to obtain imidazole-biscage boronic acid ester;

[0029] Step A3: Under nitrogen atmosphere, mix 2.4 mL of 3-chloropropyltriethoxysilane, 100 mL of DMF and 1.5 mL of triethylamine and stir until homogeneous. Add 5.24 g of imidazole-biscage borate ester and heat to 85 °C and reflux for 4 h. Then, evaporate by rotary evaporation and dry to obtain the modifier.

[0030] Step A4: Mix 12g tetraethyl orthosilicate, 8g dimethyldimethoxysilane and 40mL ethanol evenly, introduce nitrogen gas, add 3.5g water, heat to 60℃ and reflux for 1h, then add 8g modifier, maintain the temperature and reflux for 2h, and rotary evaporate to obtain hyperbranched organosilicon.

[0031] Example 2: Hyperbranched organosilicon was prepared by the following steps:

[0032] Step A1: Mix 0.03 mol boric acid and 50 mL toluene and stir until homogeneous. Add 0.03 mol pentaerythritol and heat to 110 °C. Recycle under constant temperature and reflux for 9 h. Remove toluene and water by azeotropic distillation. Add 1.5 g sodium hydroxide and 50 mL tetrahydrofuran. Purge with nitrogen gas and heat and stir until refluxed. Add 0.015 mol 3,5-dibromoaniline and reflux for 3.5 h. Wash, dry with anhydrous sodium sulfate, and distill under reduced pressure to obtain amino-terminated bis-cage borate ester.

[0033] Step A2: Disperse 2.7 mL of 1,4-dichlorobutane and 1.8 g of sodium hydroxide evenly in 100 mL of DMF, add 1.36 g of imidazole, heat to 45 °C and stir for 24 h, then add 7.32 g of terminal amino-biscage boronic acid ester and the remaining 1.8 g of sodium hydroxide, heat to 70 °C and stir for 4 h, distill under reduced pressure and dry to obtain imidazole-biscage boronic acid ester;

[0034] Step A3: Under nitrogen atmosphere, mix 3.6 mL of 3-chloropropyltriethoxysilane, 100 mL of DMF and 2.25 mL of triethylamine and stir until homogeneous. Add 7.86 g of imidazole-biscage borate ester and heat to 85 °C and reflux for 4 h. Then, evaporate by rotary evaporation and dry to obtain the modifier.

[0035] Step A4: Mix 16g tetraethyl orthosilicate, 12g dimethyldimethoxysilane and 40mL ethanol evenly, purge with nitrogen, add 5g water, and heat to 60℃ and reflux for 1.5h. Then add 12g modifier, maintain the temperature and reflux for 2.5h, and rotary evaporate to obtain hyperbranched organosilicon.

[0036] Example 3: Hyperbranched organosilicon was prepared by the following steps:

[0037] Step A1: Mix 0.04 mol boric acid and 50 mL toluene and stir until homogeneous. Add 0.04 mol pentaerythritol and heat to 110 °C. Recycle under constant temperature and reflux for 10 h. Remove toluene and water by azeotropic distillation. Add 2 g sodium hydroxide and 50 mL tetrahydrofuran. Purge with nitrogen gas and heat and stir until refluxed. Add 0.02 mol 3,5-dibromoaniline and reflux under condensation for 4 h. Wash, dry with anhydrous sodium sulfate, and distill under reduced pressure to obtain amino-terminated bis-cage borate ester.

[0038] Step A2: Disperse 4.1 mL of 1,4-dichlorobutane and 2.7 g of sodium hydroxide evenly in 100 mL of DMF, add 2.04 g of imidazole, heat to 45 °C and stir for 24 h, then add 10.1 g of terminal amino-biscage boronic acid ester and the remaining 2.7 g of sodium hydroxide, heat to 70 °C and stir for 5 h, distill under reduced pressure and dry to obtain imidazole-biscage boronic acid ester;

[0039] Step A3: Under nitrogen atmosphere, mix 4.8 mL of 3-chloropropyltriethoxysilane, 100 mL of DMF and 3 mL of triethylamine and stir until homogeneous. Add 10.5 g of imidazole-biscage borate ester and heat to 85 °C and reflux for 4 h. Then, evaporate by rotary evaporation and dry to obtain the modifier.

[0040] Step A4: Mix 20g tetraethyl orthosilicate, 15g dimethyldimethoxysilane and 40mL ethanol evenly, introduce nitrogen gas, add 6.5g water, heat to 60℃ and reflux for 2h, then add 16g modifier, maintain the temperature and reflux for 3h, and rotary evaporate to obtain hyperbranched organosilicon.

[0041] Example 4: A production process for a corrosion-resistant concrete material includes the following steps:

[0042] 70 parts silicate cement, 175 parts coarse aggregate, 80 parts fine aggregate, 10 parts fly ash, 5 parts slag powder, 3 parts hyperbranched organosilicon prepared in Example 1, 1.5 parts water-reducing agent, and 35 parts water.

[0043] Step S1: Weigh the raw materials according to the weight parts, and mix the silicate cement, coarse aggregate, fine aggregate, fly ash and slag powder evenly to obtain the mixture;

[0044] Step S2: Add water-reducing agent, hyperbranched organosilicon prepared in Example 1, and water to the mixture and stir to obtain corrosion-resistant concrete material.

[0045] Example 5: A production process for a corrosion-resistant concrete material includes the following steps:

[0046] 80 parts silicate cement, 190 parts coarse aggregate, 95 parts fine aggregate, 12 parts fly ash, 7.5 parts slag powder, 4.5 parts hyperbranched organosilicon prepared in Example 2, 2.5 parts water-reducing agent, and 40 parts water.

[0047] Step S1: Weigh the raw materials according to the weight parts, and mix the silicate cement, coarse aggregate, fine aggregate, fly ash and slag powder evenly to obtain the mixture;

[0048] Step S2: Add water-reducing agent, hyperbranched organosilicon prepared in Example 2, and water to the mixture and stir to obtain corrosion-resistant concrete material.

[0049] Example 6: A production process for a corrosion-resistant concrete material includes the following steps:

[0050] 90 parts silicate cement, 205 parts coarse aggregate, 110 parts fine aggregate, 15 parts fly ash, 10 parts slag powder, 6 parts hyperbranched organosilicon prepared in Example 3, 3.5 parts water-reducing agent, and 45 parts water.

[0051] Step S1: Weigh the raw materials according to the weight parts, and mix the silicate cement, coarse aggregate, fine aggregate, fly ash and slag powder evenly to obtain the mixture;

[0052] Step S2: Add water-reducing agent, hyperbranched organosilicon prepared in Example 3, and water to the mixture and stir to obtain corrosion-resistant concrete material.

[0053] Comparative Example 1: This comparative example is a concrete material. The difference from Example 6 is that the hyperbranched organosilicon prepared in Example 3 was not added. All other aspects are the same.

[0054] Comparative Example 2: This comparative example is a concrete material. The difference between this example and Example 6 is that organosilicon is used instead of the hyperbranched organosilicon prepared in Example 3. All other aspects are the same.

[0055] The above-mentioned organosilicon was prepared by the following steps: 20g of tetraethyl orthosilicate, 25g of dimethyldimethoxysilane and 40mL of ethanol were mixed and stirred evenly, nitrogen gas was introduced, 6.5g of water was added, and the mixture was heated to 60℃ and refluxed for 5h. The mixture was then rotary evaporated to obtain hyperbranched organosilicon.

[0056] The concrete materials prepared in Examples 4-6 and Comparative Examples 1-2 were poured into molds and cured for 28 days before being demolded and samples were taken for performance testing.

[0057] (1) The compressive strength and flexural strength of the specimens were tested according to GB / T 50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete";

[0058] (2) The samples were subjected to chloride ion penetration test and sulfate corrosion resistance test (200 times) in accordance with GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete".

[0059] The test results are shown in Table 1:

[0060] Table 1: Performance Test Results

[0061]

[0062] As can be seen from Table 1, after 28 days of curing, the compressive strength of the concrete material prepared by this invention is in the range of (56.5-58.1) MPa, the flexural strength is in the range of (19.7-21.4) MPa, the electrical flux is in the range of (418.9-452.4) C, and the corrosion resistance coefficient is in the range of (92.4-94.7)%. This indicates that the concrete material not only has good strength but also excellent corrosion resistance.

[0063] The above content is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the scope defined by the inventive concept, they should all fall within the protection scope of the present invention.

Claims

1. A corrosion-resistant concrete material, characterized in that, The raw materials include the following parts by weight: 70-90 parts silicate cement, 175-205 parts coarse aggregate, 80-110 parts fine aggregate, 10-15 parts fly ash, 5-10 parts slag powder, 3-6 parts hyperbranched organosilicon, 1.5-3.5 parts water-reducing agent, and 35-45 parts water. The hyperbranched organosilicon is prepared by hydrolysis and condensation reaction of tetraethyl orthosilicate, dimethyldimethoxysilane and a modifier. The modifier is prepared by reflux reaction of 3-chloropropyltriethoxysilane and imidazole-biscage boronic acid ester at 85°C for 4 hours. The imidazole-biscage boronic acid ester is prepared by reacting 1,4-dichlorobutane and imidazole at 45°C for 24 hours, followed by reaction with terminal amino-biscage boronic acid ester at 70°C for 3-5 hours. The terminal amino-biscage boronic acid ester is prepared by reflux reaction of pentaerythritol and boric acid at 110°C for 8-10 hours, followed by reflux reaction with 3,5-dibromoaniline for condensation and reflux for 3-4 hours.

2. The corrosion-resistant concrete material according to claim 1, characterized in that, The hyperbranched organosilicon is prepared by the following steps: Step A1: Mix boric acid and toluene evenly, add pentaerythritol, heat to 110℃, reflux at constant temperature for 8-10 hours, remove toluene and water by azeotropic distillation, add sodium hydroxide and tetrahydrofuran, purge with nitrogen gas, heat and stir until reflux, add 3,5-dibromoaniline, reflux for 3-4 hours, wash, dry with anhydrous sodium sulfate, and distill under reduced pressure to obtain amino-terminated bis-cage borate ester; Step A2: Disperse 1,4-dichlorobutane and half a part of sodium hydroxide evenly in DMF, add imidazole, heat to 45°C and stir for 24 hours, then add terminal amino-biscage boronic acid ester and the remaining half part of sodium hydroxide, heat to 70°C and stir for 3-5 hours, distill under reduced pressure and dry to obtain imidazole-biscage boronic acid ester. Step A3: Under nitrogen atmosphere, 3-chloropropyltriethoxysilane, DMF and triethylamine are mixed and stirred evenly, imidazole-biscage boronic acid ester is added, and the mixture is heated to 85°C and refluxed for 4 hours. The mixture is then rotary evaporated and dried to obtain the modifier. Step A4: Mix tetraethyl orthosilicate, dimethyldimethoxysilane and ethanol evenly, introduce nitrogen gas, add water, and heat to 60°C and reflux for 1-2 hours. Then add the modifier, maintain the temperature and reflux for 2-3 hours, and rotary evaporate to obtain hyperbranched organosilicon.

3. The corrosion-resistant concrete material according to claim 2, characterized in that, In step A1, the ratio of boric acid, toluene, pentaerythritol, sodium hydroxide, tetrahydrofuran, and 3,5-dibromoaniline is 0.02-0.04 mol: 50 mL: 0.02-0.04 mol: 1-2 g: 50 mL: 0.01-0.02 mol.

4. The corrosion-resistant concrete material according to claim 2, characterized in that, In step A2, the ratio of 1,4-dichlorobutane, sodium hydroxide, DMF, imidazole and dicage-like borate ester is 1.34-4.1 mL: 1.8-5.4 g: 100 mL: 0.68-2.04 g: 3.66-10.1 g.

5. The corrosion-resistant concrete material according to claim 2, characterized in that, In step A3, the ratio of 3-chloropropyltriethoxysilane, DMF, triethylamine and imidazole-bis-cage borate ester is 2.4-4.8 mL: 100 mL: 1.5-3 mL: 5.24-10.5 g.

6. The corrosion-resistant concrete material according to claim 2, characterized in that, In step A4, the ratio of tetraethyl orthosilicate, dimethyldimethoxysilane, ethanol, water and modifier is 12-20g:8-15g:40mL:3.5-6.5g:8-16g.

7. The corrosion-resistant concrete material according to claim 1, characterized in that, The coarse aggregate is crushed stone with a particle size of 12-25mm, and the fine aggregate is sand with a particle size of 2-6mm.

8. The corrosion-resistant concrete material according to claim 1, characterized in that, The water-reducing agent is tartaric acid.

9. A production process for the corrosion-resistant concrete material according to any one of claims 1-8, characterized in that, Includes the following steps: Step S1: Weigh the raw materials according to the weight parts, and mix the silicate cement, coarse aggregate, fine aggregate, fly ash and slag powder evenly to obtain the mixture; Step S2: Add water-reducing agent, hyperbranched organosilicon and water to the mixture and stir to obtain corrosion-resistant concrete material.